Weight Loss and Malnutrition in Patients with Parkinson's Disease: Current Knowledge and Future Prospects - Ma, Kai; Xiong, Nian; Shen, Yan; Han, Chao; Liu, Ling; Zhang, Guoxin; Wang, Luxi; Guo, Shiyi; Guo, Xingfang; Xia, Yun; Wan, Fang; Huang, Jinsha; et al. (Frontiers in Aging Neuroscience, 2018)
Parkinson's Disease (PD) is currently considered a systemic neurodegenerative disease manifested with not only motor but also non-motor symptoms. In particular, weight loss and malnutrition, a set of frequently neglected non-motor symptoms, are indeed negatively associated with the life quality of PD patients. Moreover, comorbidity of weight loss and malnutrition may impact disease progression, giving rise to dyskinesia, cognitive decline and orthostatic hypotension, and even resulting in disability and mortality. Nevertheless, the underlying mechanism of weight loss and malnutrition in PD remains obscure and possibly involving multitudinous, exogenous or endogenous, factors. What is more, there still does not exist any weight loss and malnutrition appraision standards and management strategies. Given this, here in this review, we elaborate the weight loss and malnutrition study status in PD and summarize potential determinants and mechanisms as well. In conclusion, we present current knowledge and future prospects of weight loss and malnutrition in the context of PD, aiming to appeal clinicians and researchers to pay a closer attention to this phenomena and enable better management and therapeutic strategies in future clinical practice.